Effect of Sonneratia alba Leaf Extract on Antioxidant Activity and Moisturizer Gel Properties - Rahmiati Molamahu; Faiza A. Dali; Sri Rahayu Kalaka (Information Technology and Science (ITScience), 2026)
The skin functions as the primary barrier against environmental stressors, where ultraviolet radiation and pollutants induce oxidative stress and accelerate premature aging. Although Sonneratia alba leaves possess considerable antioxidant potential, information regarding their application in moisturizer gel formulations remains limited. This study evaluated the effect of different concentrations of S. alba leaf extract on the antioxidant activity and physical properties of a moisturizer gel. A completely randomized design was employed using extract concentrations of 0% (control), 10%, 15%, and 20% (w/w) incorporated into a Carbopol-based gel formulation. Antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, while viscosity and spreadability were evaluated as physical quality parameters. The results showed that antioxidant activity ranged from 72.41% to 73.11% inhibition, with no significant differences among extract concentrations (p > 0.05), indicating that antioxidant capacity was maintained after gel formulation. In contrast, increasing extract concentration significantly reduced viscosity (p < 0.05) and significantly affected horizontal spreadability, whereas vertical spreadability remained unchanged. These findings suggest that S. alba extract modified the rheological characteristics of the gel without compromising its antioxidant activity. The formulation containing 20% extract exhibited the highest mean antioxidant activity while maintaining acceptable physical characteristics, indicating its potential as a natural active ingredient for antioxidant moisturizer gel formulations.